Knowledge on sexually transmitted diseases: results from a survey among Italian university students. (20th October 2021) - Tocco Tussardi, I; Mazzi, M; Benoni, R; Astorino, G; Fila, A; Tardivo, S; Majori, S; Busch, IM; Rimondini, M; Moretti, F
Abstract: Background: Sexually transmitted diseases (STDs) are one of the most pressing public health concerns in many countries. Adolescents and young adults are the most affected population. Given that risky sexual behaviors are a growing trend, awareness must be increased. To identify the most important issues contributing to STDs spreading in the young population, we designed a project aimed to explore knowledge, attitudes, and behaviors related to STDs among students from an Italian University. As part of this bigger project, the present study focused on data regarding knowledge, information/education sources, and awareness on non-sexual ways of transmission. Methods: A descriptive, cross-sectional study was carried out at the University of Verona, Italy. An ad-hoc questionnaire was developed based on existing literature and expert consensus and was administered to the students from December 2, 2020 to January 7, 2021. The project was approved by the Committee for Human Research of the University of Verona. Results: A total number of 2258 individuals (76% women) answered the survey. Results were not quite satisfactory, especially regarding the knowledge on ways of STD transmission and carcinogenic viruses, and students showed misperceptions about general knowledge related to STDs. The study also demonstrated that students collect information on STDs primarily from the internet but would turn to a specialist in case of doubt. Misbeliefs regarding non-sexual ways of transmission were observed. Regarding differences between genders, the female population was tendentially more aware of the link between Papilloma Virus infection and cancer. Conclusions: This study indicates that current educational efforts to disseminate knowledge on STDs and thus contain infections are not sufficient. To prevent future spreading of STDs, information activities regarding STDs should be increased and health education in schools and universities promoted. Key messages: Early information and education are among the pillars of controlling the spread of STDs, but at the moment they still seem to need better implementation. Assessing which areas of knowledge must be improved in different groups can facilitate the development of targeted interventions to achieve better results in terms of disease awareness and prevention.